Instruments for evaluating the parental emotional status and ecological support systems among parents who considered cochlear implantation for their children with hearing loss: A scoping review. - Tang Zhi Lim; Cila Umat; Pei-Hua Chen; Chun Hong Gan; Bee See Goh (PLoS ONE)
Objectives Parents of children diagnosed with severe-to-profound sensorineural hearing loss may experience a range of emotions owing to a lack of knowledge and experience in dealing with such children. However, most audiology clinics only attend to children with deaf and hard of hearing (DHH) and not their parents. Thus, parents' emotional and support needs are frequently excluded from the intervention sessions, making their own needs invisible. This study aimed to identify academic and clinical instruments used for assessing parental emotional status (PES) and ecological support systems (ESS) in early intervention and determine the factors affecting PES and ESS among parents of DHH children undergoing cochlear implantation. Materials and methods This scoping review followed the rigorous methodological framework; searched Medline (via OVID and EMBSCO), Scopus, and Web of Science; and selected studies relevant to validated instruments used to evaluate the PES and ESS among parents of DHH children below 6 years old. Before selecting and reviewing relevant articles, two reviewers independently assessed article titles and abstracts from the data sources. Two reviewers verified half of the first reviewer's extracted data. Results Overall, 3060 articles were retrieved from the database search, and 139 were selected for full-text review following title and abstract reviews. Ultimately, this study included 22 articles. Among them, 23 and 12 validated instruments, most of which are generic measures, were used for assessing PES and ESS, respectively. Three condition-specific instruments were identified and designed to be administered following cochlear implantation surgery. Conclusions This study revealed that healthcare professionals who interact with parents of DHH children lack the necessary instruments, particularly for parents of children undergoing cochlear implantation surgery. Therefore, it is necessary to develop condition-specific instruments for parents who consider cochlear implantation for their children.